Efficient Schemes for Securing Network Coding Against Wiretapping - Liu, Guangjun; Zhou, Hang (Wuhan University journal of natural sciences, 2013)
Existing solutions for secure network coding either bring significant bandwidth overhead or incur a high computational complexity. For exploiting low-overhead mechanism for secure network coding against wiretapping, three efficient schemes are proposed for the applications with different security requirements. The basic idea behind this paper is first to encrypt a small part of source vectors and then subject the remaining original source vectors and the encrypted vectors to a special linear transformation. Also, a lightweight version of this scheme is then presented for resource-constrained networks. Moreover, an extensive scheme with enhanced security is also considered. All proposals are shown to have properties of lower security complexity and smaller bandwidth usage compared with the existing solutions. Also, the proposals can be easy to achieve flexible levels of security for various applications.